ANÁLISE E DESENVOLVIMENTO DE CONVERSORES ESTÁTICOS PARA APLICAÇÕES DE MÉDIA TENSÃO - ANO II - FEYH, ANDRESSA R.; RECH, CASSIANO; SALVADORI, FABIANO; LEANDRO, GIDEON V.; SILVA, GUILHERME S. D.; BOLACELL, JULIO C. O.; CAMPOS, MAURÍCIO D.; CAMARGO, ROBINSON F. D. (Salão do Conhecimento, 2013)
Resumo